Effects of single and combined toxic exposures on the gut microbiome: Current knowledge and future directions. (15th September 2019) - Tsiaoussis, John; Antoniou, Michael N.; Koliarakis, Ioannis; Mesnage, Robin; Vardavas, Constantine I.; Izotov, Boris N.; Psaroulaki, Anna; Tsatsakis, Aristidis
Graphical abstract: Highlights: Xenobiotics affect the gut microbiome influencing development of metabolic diseases Xenobiotics have unpredictable effects on the gut microbiome. More studies are needed to simulate real-life exposure scenarios. Abstract: Human populations are chronically exposed to mixtures of toxic chemicals. Predicting the health effects of these mixtures require a large amount of information on the mode of action of their components. Xenobiotic metabolism by bacteria inhabiting the gastrointestinal tract has a major influence on human health. Our review aims to explore the literature for studies looking to characterize the different modes of action and outcomes of major chemical pollutants, and some components of cosmetics and food additives, on gut microbial communities in order to facilitate an estimation of their potential mixture effects. We identified good evidence that exposure to heavy metals, pesticides, nanoparticles, polycyclic aromatic hydrocarbons, dioxins, furans, polychlorinated biphenyls, and non-caloric artificial sweeteners affect the gut microbiome and which is associated with the development of metabolic, malignant, inflammatory, or immune diseases. Answering the question 'Who is there?' is not sufficient to define the mode of action of a toxicant in predictive modeling of mixture effects. Therefore, we recommend that new studies focus to simulate real-life exposure to diverse chemicals (toxicants, cosmetic/food additives), including as mixtures, and which combine metagenomics, metatranscriptomics and metabolomic analytical methods achieving in that way a comprehensive evaluation of effects on human health.